Comparison of 2D and 3D gamma evaluation method in patient speciﬁc intensity-modulated radiotherapy quality assurance - Shukla, Arvind Kumar; Bhamra, Hartanya Kaur; Rathore, Narendra Kumar; Patidar, Arvind Kumar; Verma, Atul; Rajpurohit, Vikram Singh; Dangayach, Suresh Kumar; Chaudhary , Bhupendra S. (International Journal of Research in Medical Sciences, 2023)
Background: In this study we have compared 2D and 3D gamma pass percentage for a variety of acceptance criteria for 40 step-and-shoot IMRT (intensity-modulated radiotherapy) plans. Methods: Treatment planning was done for 40 patient including head and neck, abdomen and pelvis simulated on the Siemens Healthcare GmBH CT simulator with images of 3 mm slice thickness using treatment planning system (TPS) (Monaco Version 5.11.03, Elekta medical system) using Monte Carlo algorithm. The gamma evaluation was done using PTW VeriSoft 8.1 which allowed us to perform 2D and 3D gamma index calculation, slice-by-slice comparison of measured and calculated dose distributions, measured dose was compared against the calculated DICOMRT dose on the OCTAVIUS 3D phantom from TPS. Results: The average 3D and 2D gamma passing in coronal planes were 96.61±0.45% and 96.27±0.78% for 5 mm/5% criteria, 93.74±4.17% and 91.9±4.88% for 3 mm/3% criteria, 85.83±7.58% and 82.41±8.06% for 2 mm/2% criteria and 62.8±9.42% and 59.18±9.52% for 1 mm/1% criteria respectively for all cases. The average gamma passing rate for 3D gamma analysis was 0.35%, 1.97 %, 3.97% and 5.78% higher when compared with 2D coronal planar analyses for 5 mm/5%, 3 mm/3%, 2 mm/2% and 1 mm/1% DTA criteria respectively. Conclusions: It is concluded in the study that 3 D gamma passing rate is higher compared to 2D gamma passing for head and neck, abdomen and pelvis cases.